When Do the Leaves Fall and When Do We Reap? – Semantic Analysis of Folk Month Names in the Languages of Eastern Europe - Sučević Međeral, Krešimir (Research in Language, 2021)
The abundance of folk month names in different languages of Eastern Europe results in specific mental pictures in a speaker's mind. Translation usually fails to communicate the elaborate connotations implied, even in the case of closely related languages. The paper gives a comparative semantical analysis of folk month names in the Slavic languages, the Baltic languages, Finnish, Estonian, Hungarian, Romanian and Albanian, identifying the common features, the differences and possible reasons for both. The aim of the paper is to provide data for both linguistic and ethnological mapping of Eastern Europe, as an area that had been under less influence from the Latin-dominated culture and had in that way better preserved some original, less uniform linguistic features.